Does adverse selection matter? Evidence from a natural experiment - Erik Grönqvist (Stockholm School of Economics, The Economic Research Institute (EFI), 2004)
The empirical evidence of adverse selection in insurance markets is mixed. The problem in assessing the extent of adverse selection is that private information, on which agents act, is generally unobservable to the researcher, which makes it difficult to distinguish between adverse selection and moral hazard. Unique micro data, from a dental insurance natural experiment, is here used to provide a direct test of selection. All agents in a population were stratified into different risk classes, and were unexpectedly given the opportunity to insure their dental care costs. The setup of the insurance makes it possible to observe a proxy for private information. Interestingly, results differ across risk classes. Within high-risk classes, there is evidence of adverse selection and within low-risk classes, the results, surprisingly, indicate an advantageous selection. This dual selection can explain the limited empirical evidence for adverse selection in insurance markets in the literature: the two effects may balance out on the aggregate level. The paper also presents a model of insurance choice that can harbor both adverse and advantageous selection. The pattern in the data is explained by differences in the effectiveness of prevention across high and low risk classes.
Keywords: D81; D82; G22; I11; 330; Asymmetric information; Adverse Selection; Advantageous Selection; Health Insurance; Adverse Selection; Asymmetrische Information; Private Krankenversicherung; Theorie; Dentalprodukt